Brazilian Post Graduation Degree Studies: Evolution and Main Challenges in the Prospective Scenarios Environment - Moritz, Gilberto de Oliveira; Pereira, Mauricio Fernandes; Moritz, Mariana Oliveira; Maccari, Emerson Antonio (Future Studies Research Journal: Trends and Strategies, 2013)
This article aims to examine the evolution of post-graduation courses, as from its creation to the present day, based on the work undertaken by the Coordination of Higher Education Personnel Improvement - CAPES and the National Council for Scientific and Technological Development - CNPq, identifying the most important variables in the environment and its perspectives in the environments of future scenarios. It is also noteworthy that today the country goes through a period of the greatest breadth and importance of the post-graduation courses, a sector that consolidated itself for possessing national and international high qualification. In the present study, we proceed to the bibliographical review and to the documentary examination, to rescue the history of post-graduation degree courses and their main challenges, substantiated in an analysis involving variables that leads to the future of this environment, seeking through the methodology of prospective scenarios, to establish strategies for the continuity of these best practices in the future.